No blank slates: Pre-existing schemas about pharmaceuticals predict memory for side effects. Issue 4 (3rd April 2017) - Heller, Monika K.; Chapman, Sarah C.E.; Horne, Rob
Abstract : Objectives: Attribution of symptoms as medication side effects is informed by pre-existing beliefs about medicines and perceptions of personal sensitivity to their effects (pharmaceutical schemas). We tested whether (1) pharmaceutical schemas were associated with memory (recall/recognition) for side effect information (2) memory explained the attribution of a common unrelated symptom as a side effect. Design: In this analogue study participants saw the patient leaflet of a fictitious asthma drug listing eight side effects. Main outcome measures: We measured recall and recognition memory for side effects and used a vignette to test whether participants attributed an unlisted common symptom (headache) as a side effect. Results: Participants who perceived pharmaceuticals as more harmful in general recalled fewer side effects correctly ( r Correct Recall  = −.273), were less able to differentiate between listed and unlisted side effects ( r Recognition Sensitivity  = −.256) and were more likely to attribute the unlisted headache symptom as a side effect ( r side effect attribution  = .381, p s < .01). The effect of harm beliefs on side effect attribution was partially mediated by correct recall of side effects. Conclusion: Pharmaceutical schemas are associated with memory for side effect information. Memory may explain part of the association between pharmaceutical schemas and the attribution of unrelated symptoms as side effects.